Aktivitas Antifungi Ekstrak Etanol dan Metanol Batang Pisang Mauli 100% - Apriasari, Maharani Laillyza (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2015)
Background: North Hulu Sungai Banjarmasin people are using banana stem mauli to accelerate wound healing in the skin. Mauli banana stem extract contains antimicrobial and antioxidant effects. Need the development of traditional plants that can be used as a topical antiseptic drug in the oral cavity. Purpose: to determinethe anti fungal effectivity of methanolextractof 100% mauli banana stem compared with the ethanol extractof 100% mauli banana stem. Methods and materials: pure laboratory experimental research with the completely randomized designusing 3 treatments with 9 replications. Making 100% banana mauli stemextractby maceration method using the solution of ethanol and methanol.The sample wasa pure culture of Candida albicans. Saboroud agar petridish were contained Candida albicans that have given filter paper soaked for 3 hours with100% methanol extract of mauli banana stem, 100% ethanol extract of mauli banana stem, and 0,2% Clorhexidine gluconate. Inhibition zone diameter of three treatments was compared after doing incubation for 1 day. It using the diffusion method. Results: Kruskal Wallis test of the three treatment resulted p value=0.00(p <0.05) that H0 was rejected, so i tcould be concluded that there were significant differences between the three treatments. Mann Whitney test resulted that the treatment of 100% ethanol was compared with100% methanol resulted p = 0.00 (p <0.05).There was a significant difference between the treatmentof 100% ethanoland 100% methanol to the growthness of Candida albicans.Conclusion: The results ofthe studyit appears that the banana stem mauli have antimicrobial activity. Methanol extract of banana stem mauli has a total flavonoids was higher than the ethanol extractof banana stem mauli. This makes methanol extracts had higher antifungal activity than the ethanol extract. Key words : Antifungal, Diffusion method, Ethanol, Extract, Mauli banana stem, Methanol.